Manajemen Kurikulum Sekolah Dasar Islam Terpadu (SDIT) Anak Soleh 1 Mataram - Ihwan (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
This study used qualitative research methods and research results are presented in descriptive form. Data collection techniques using observation, interviews, and documentation. The data analysis used in this study is an interactive model from Miles and Huberman, namely by reducing data, the presentation of this research by curriculum management in managing superior programs at SDIT Anak Soleh 1 Mataram. The results are implemented by the head of the madrasa by fulfilling the stages of the strategic management process which consists of (1) Planning an integrated curriculum at SDIT Anak Soleh 1 Mataram carried out in a curriculum planning team meeting at the beginning of the semester. The steps for planning an integrated curriculum consist of making annual programs (prota), making semester programs (prosem), syllabus and lesson plans. The curriculum planning of SDIT Anak Soleh 1 Mataram by formulating of 2013 curriculum with the JSIT curriculum. (2) The implementation of the integrated curriculum at SDIT Anak Soleh 1 Mataram is carried out by using two methods, the first: integration of the 2013 curriculum with the JSIT curriculum through integration of themes, integration of Islamic values, integration of practice in the learning cycle in the classroom and outside the classroom, second: development of school programs through religious programs such as tahsin Al-qur'an with WAFA method, tahfiz Al-qur'an, dhuha prayer in congregation, cheerful romadon, infaq, and caring qurban. (3) Evaluation of the integrated curriculum of SDIT Anak Soleh 1 Mataram through daily, formative, and summative evaluations. Daily evaluation to see the achievement of daily activity targets such as evaluating the tahsin of the Qur'an. Weekly evaluation to see the achievement of weekly activity targets such as the tahfiz Al-qur'an program. Formative evaluation through the Mid-Semester Examination (UTS) and summative evaluation through the Final Semester Examination (UAS).